The Impact of Gold Mining on Community Income in Poboya Village, Mantikulore District, Palu City - Selawati, S.; Rafika, Ika (Manunggal Halim Jaya, 2024)
The purpose of this study was to determine the impact of gold mining on community income in Poboya Village, Mantikulore sub-district, Palu City. This research was conducted using qualitative and quantitative research methods. The data sources used in this research are primary data and secondary data with data collection techniques, namely observation, interviews and documentation, the data obtained is then analyzed into a conclusion from the research process. The findings of the study found that the Impact of Gold Mining on Community Income in Poboya Village, Mantikulore District, Palu City had a positive impact and a negative impact on mining. The positive impact of gold mining can improve the economy of miners, while the negative impact poses a greater danger, especially the impact on the environment.